2015
DOI: 10.18632/oncotarget.6249
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of CX43 on stromal cells promotes leukemia apoptosis

Abstract: Connexin 43 (Cx43) induced apoptosis has been reported in solid tumors, but the effect of Cx43 expressed by bone marrow stromal cells (BMSC) in leukemia has not been fully investigated. Manipulating Cx43 expression could be a potential therapeutic strategy for leukemia. Here, we investigate the effect of Cx43 expressed by BMSCs (human Umbilical Cord Stem Cells over-expressed CX43, Cx43-hUCSC) on leukemia cells. When co-cultured with Cx43-hUCSC, leukemia cells show significant lower growth rate with increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…UC-MSCs coculured with breast cancer cell line MDA-MB-231 can spontaneously generate hybrid/chimeric cell populations and induce expression of the GPI-anchored CD90 molecule in breast cancer cells, which can be partially blocked by a gap junction inhibitor in vitro and in vivo , leading to stimulation of breast cancer cell growth 70. Our previous study showed that increased expression of CX43 on UC-MSCs promotes leukemia apoptosis 71.…”
Section: The Mechanism Of Mscs In Anticancer Therapiesmentioning
confidence: 99%
“…UC-MSCs coculured with breast cancer cell line MDA-MB-231 can spontaneously generate hybrid/chimeric cell populations and induce expression of the GPI-anchored CD90 molecule in breast cancer cells, which can be partially blocked by a gap junction inhibitor in vitro and in vivo , leading to stimulation of breast cancer cell growth 70. Our previous study showed that increased expression of CX43 on UC-MSCs promotes leukemia apoptosis 71.…”
Section: The Mechanism Of Mscs In Anticancer Therapiesmentioning
confidence: 99%
“…In contrast, others have reported that reduced Cx43 expression or deterioration of GJIC in BMSC is associated with leukemogenesis, while the upregulation of Cx43 GJIC in BMSC after chemotherapy or transfection with the Cx43 gene induces caspase 3 and 7 mediated apoptosis, and enhances the efficacy of therapies in hematologic malignancies [157][158][159][160][161]. In a minimal residual disease mouse model, the relapse of leukemia was delayed when mice were transplanted with human umbilical cord blood progenitors overexpressing Cx43 [160]. An antiproliferative effect of Cx43 was also observed in the U937 AML cell line expressing the AML1-ETO fusion protein, and it was mediated by the accumulation of p27 kip1 protein [162].…”
Section: Role Of Gap Junctions In Leukemic Hematopoiesismentioning
confidence: 95%
“…Of note, in vitro studies using OCI-AML3 and OCIM2 AML cell lines suggest that the higher expression of Cx43 in OCI-AML3 cells acts as a tumor promoter, which exerts its effect by promoting the exchange of growth factors; or by facilitating malignant cell proliferation and survival signal [156]. In contrast, others have reported that reduced Cx43 expression or deterioration of GJIC in BMSC is associated with leukemogenesis, while the upregulation of Cx43 GJIC in BMSC after chemotherapy or transfection with the Cx43 gene induces caspase 3 and 7 mediated apoptosis, and enhances the efficacy of therapies in hematologic malignancies [157][158][159][160][161]. In a minimal residual disease mouse model, the relapse of leukemia was delayed when mice were transplanted with human umbilical cord blood progenitors overexpressing Cx43 [160].…”
Section: Role Of Gap Junctions In Leukemic Hematopoiesismentioning
confidence: 99%
“…In contrast, loss of direct cell–cell interaction and the lack of electrical coupling in cells are common features in many tumors. While tumor‐promoting chemicals and oncogenes inhibit GJIC, antitumor chemicals and anti‐oncogene drugs were associated with growth control and loss of tumorigenicity by re‐gaining GJIC activity . Moreover, the key proteins involved in GJIC, connexins are emerging as tumor suppressors .…”
Section: The Upr In the Regulation Of Tumor Microenvironmentmentioning
confidence: 99%